2009
DOI: 10.1186/1471-2407-9-54
|View full text |Cite
|
Sign up to set email alerts
|

Arrested neural and advanced mesenchymal differentiation of glioblastoma cells-comparative study with neural progenitors

Abstract: BackgroundAlthough features of variable differentiation in glioblastoma cell cultures have been reported, a comparative analysis of differentiation properties of normal neural GFAP positive progenitors, and those shown by glioblastoma cells, has not been performed.MethodsFollowing methods were used to compare glioblastoma cells and GFAP+NNP (NHA): exposure to neural differentiation medium, exposure to adipogenic and osteogenic medium, western blot analysis, immunocytochemistry, single cell assay, BrdU incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 22 publications
(60 reference statements)
4
41
0
Order By: Relevance
“…Multiplex PCR was performed for evaluation of EGFR amplification with superoxide dismutase 1 (SOD1) used as a reference gene as described previously [28].…”
Section: Egfr Amplification Analysismentioning
confidence: 99%
“…Multiplex PCR was performed for evaluation of EGFR amplification with superoxide dismutase 1 (SOD1) used as a reference gene as described previously [28].…”
Section: Egfr Amplification Analysismentioning
confidence: 99%
“…EMT and mesenchymal-epithelial transition (MET) are key regulators of cellular plasticity in carcinomas and play a key role in treatment resistance, tumor recurrence, and metastatic progression [38]. Recent studies have shown that GBs have mesenchymal properties [39][40][41][42][43][44]. However, the normal CGH array profile of GASCs, contrasting with the abnormal profile of GB tumor cells, is not consistent with this hypothesis.…”
Section: Origins Of Gascsmentioning
confidence: 99%
“…There is an increasing body of evidence indicating that astrocytic gliomas may be derived from intermediate gliotypic neural stem cells (Walton et al, 2009). Undifferentiated cancer cells derived from GBM and glial fibrillary acidic protein (GFAP)þ normal neural progenitors maintained in culture share a ''multilineage'' antigenic phenotype (CD44þ/microtubule associated protein-2þ/GFAPþ/vimentinþ/bIII-tubulinþ/fibronectinþ) (Rieske et al, 2009). It should be noted that, GFAPþ/nestinþ/ bIII-tubulinþ cells in GBMs resemble normal human fetal astrocytes in vitro (Rieske et al, 2007;Dráberová et al, 2008) and of glial precursor or neural stem cells of the human telencephalic subventricular zones (Dráberová et al, 2008) (Fig.…”
Section: Biii-tubulin Expression and Cancer Stem Cells In Gbm?mentioning
confidence: 99%